Traditional Use of Coleus monostachyus for Wound Healing among the Dani People of Papua: An Ethnobotanical Assessment - Hans Frits Liborang; Johanis M. Ramandey; Suryadi; Ajumat Fimbay B; Wardhana W. Dharsono (Jurnal Penelitian Pendidikan IPA, 2026)
This study documents the traditional knowledge and wound-healing practices associated with Coleus monostachyus—locally known as Anggungiga—among the Dani people of Papua. Data were collected through semi-structured interviews with 34 purposively selected respondents, including traditional healers, elders, women, and youth. The results show that the leaves are exclusively used (100%), with three main preparation methods: pounding (50%), rubbing (30%), and direct application of fresh leaves (20%). The reported healing duration ranges from 2–7 days, and 85% of respondents perceived the plant to be more effective than modern medicine within their local context. Statistical analysis indicates a significant association between social roles and the diversity of preparation methods (χ² = 9.14; p = 0.027), and a positive correlation between age and knowledge variation (ρ = 0.42; p = 0.021). Ethnobotanical indices, including RFC (0.95), UV (1.20), and ICF (0.91)—demonstrate the high cultural relevance of C. monostachyus for wound treatment. These findings highlight the importance of preserving Dani ethnobotanical heritage and suggest the potential for further pharmacological exploration of this species.